Ballarat Town Hall, with a statue of Queen Victoria in foreground, Victoria, 1994 - Ellmers, Grant (1994)
Ballarat Town Hall was erected in 1870-72. This photograph shows a statue of Queen Victoria in the foreground.
Title devised by cataloguer.
Part of the collection: Ballarat, Victoria, 1994.
Also available online
Keywords: Town Hall (Ballarat, Vic.) -- Photographs; Statues -- Victoria -- Ballarat -- Photographs; Ballarat (Vic.) -- Buildings, structures, etc. -- Photographs